Metabolic signatures of performance in elite world tour professional male cyclists - Nemkov, T.; Cendali, F.; Stefanoni, D.; Martinez, J. L.; Hansen, K. C.; San-Millán, I.; D'Alessandro, A. (Sports Medicine, 2023)
Background and Objective: Metabolomics studies of recreational and elite athletes have been so far limited to venipuncture-dependent blood sample collection in the setting of controlled training and medical facilities. However, limited to no information is currently available to determine if findings in laboratory settings are translatable to a real-world scenario in elite competitions. The goal of this study was to define molecular signatures of exertion under controlled exercise conditions and use these signatures as a framework for assessing cycling performance in a World Tour competition. Methods: To characterize molecular profiles of exertion in elite athletes during cycling, we performed metabolomics analyses on blood isolated from 28 international-level, elite, World Tour professional male athletes from a Union Cycliste Internationale World Team taken before and after a graded exercise test to volitional exhaustion and before and after a long aerobic training session. Moreover, established signatures were then used to characterize the metabolic physiology of five of these cyclists who were selected to represent the same Union Cycliste Internationale World Team during a seven-stage elite World Tour race. Results: Using dried blood spot collection to circumvent logistical hurdles associated with field sampling, these studies defined metabolite signatures and fold change ranges of anaerobic or aerobic exertion in elite cyclists, respectively. Blood profiles of lactate, carboxylic acids, fatty acids, and acylcarnitines differed between exercise modes. The graded exercise test elicited significant two- to three-fold accumulations in lactate and succinate, in addition to significant elevations in free fatty acids and acylcarnitines. Conversely, the long aerobic training session elicited a larger magnitude of increase in fatty acids and acylcarnitines without appreciable increases in lactate or succinate. Comparable signatures were revealed after sprinting and climbing stages, respectively, in a World Tour race. In addition, signatures of elevated fatty acid oxidation capacity correlated with competitive performance. Conclusions: Collectively, these studies provide a unique view of alterations in the blood metabolome of elite athletes during competition and at the peak of their performance capabilities. Furthermore, they demonstrate the utility of dried blood sampling for omics analysis, thereby enabling molecular monitoring of athletic performance in the field during training and competition.